PENENTUAN KARYAWAN BERPRESTASI PT X MENGGUNAKAN METODE GAUGING ABSENCE of PREREQUISITES (GAP) - Agustina, Merry (JURNAL ILMIAH MATRIK, 2014)
Employees are a major factor in the smooth running and progress and success of a company. The leaders of the company should be able to motivate their employees to be able to work optimally and always give the best for the company. Achievement is a result of a person who assessed on the performance of the envious own personal as well as team of an entity or community. The purpose of this research is to apply the method GAP as a profile matching method in the process of determining outstanding employee at PT X. PT X conduct an assessment of achievements of its employees and as a result of assessment for employees who excellent will be given a reward. In determining and assessing the performance of each employee there are a number of assessment criteria which include Employee Attitudes, Behaviour Employees and Employee Presence.